Sosialisasi dan Workshop Penyusunan Roadmap Kajian SNI Meja dan Kursi Sekolah Tahun 2022-2024 - TIUAJ, Yanto; Hutahaean, Hotma A.; Sukwadi, Ronald; Silalahi, Agustinus (Jurnal Pengabdian Masyarakat Charitas, 2022)
This activity aimed to develop roadmap for the future study of national standard of chair and desk to be used by both researchers in the Pusat Riset Teknologi Pengujian dan Standar, Badan Riset dan Inovasi Nasional (PRTPS – BRIN) and Industrial Engineering Department, Atma Jaya Catholic University. Prior to developing roadmap, a workshop has been conducted to provide researchers with the basic knowledge of anthropometry, standardization of measurements, measurement illustrations and how to apply such data for design, in particular for school furniture design and evaluation. The roadmap could be used as guideline to conduct future research topics related to the national standard of school furniture for all level.